2017
DOI: 10.3847/1538-4357/835/2/291
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in Protoplanetary Disks around Herbig Ae/Be and T Tauri Stars

Abstract: A distinct set of broad emission features at 3. 3, 6.2, 7.7, 8.6, 11.3, and 12.7 µm, is often detected in protoplanetary disks (PPDs). These features are commonly attributed to polycyclic aromatic hydrocarbons (PAHs). We model these emission features in the infrared spectra of 69 PPDs around 14 T Tauri and 55 Herbig Ae/Be stars in terms of astronomical-PAHs. For each PPD, we derive the size distribution and the charge state of PAHs. We then examine the correlations of the PAH properties (i.e., sizes and ioniza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 297 publications
(683 reference statements)
3
90
0
Order By: Relevance
“…We have also demonstrated that CLIcK can reproduce well the entire Spitzer/IRS water emission spectrum from AA Tau, especially with the power-law temperature profile option, and correctly retrieve the parameters of the water emitting region from a reference spectrum simulated with RADLite. The framework of CLIcK can be easily generalized to solve similar problems in which the dust continuum has to be properly treated, including fitting the emission features from crystalline silicates (e.g., Juhász et al 2010) and polycyclic aromatic hydrocarbons (e.g., Seok & Li 2017) in circumstellar disks.…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated that CLIcK can reproduce well the entire Spitzer/IRS water emission spectrum from AA Tau, especially with the power-law temperature profile option, and correctly retrieve the parameters of the water emitting region from a reference spectrum simulated with RADLite. The framework of CLIcK can be easily generalized to solve similar problems in which the dust continuum has to be properly treated, including fitting the emission features from crystalline silicates (e.g., Juhász et al 2010) and polycyclic aromatic hydrocarbons (e.g., Seok & Li 2017) in circumstellar disks.…”
Section: Discussionmentioning
confidence: 99%
“…ous modelling of infrared spectra of both Oph IRS 48 and HD 169142 have indicated the likely presence of PAHs within the gas gap regions (regions depleted in CO; Geers et al 2007b;Maaskant et al 2014;Seok & Li 2017). Oph IRS 48 is located in the ρ Ophiuchus star forming region, as catalogued by Elias (1978) and confirmed by Wilking et al (1989).…”
Section: Introductionmentioning
confidence: 88%
“…Owing to its up to a factor of 100 better sensitivity than ISO/SWS, Spitzer allowed one to extend the mid-IR spectroscopy and imaging into new regimes that ISO could not probe. The Infrared Spectrograph (IRS) on board Spitzer was capable of detecting PAH emission in objects which were too faint for ISO (e.g., the PAH emission at 6-9 µm of protoplanetary disks around T Tauri stars which had previously escaped detection by ISO 46 was unambiguously detected by Spitzer/IRS [47][48][49] ; see Fig. 1e).…”
Section: The Spitzer Legacy Of Pah Astrophysicsmentioning
confidence: 99%